US college radio, the 'New British Invasion' and media alterity. - Rubin, Nick (Radio Journal: International Studies in Broadcast & Audio Media, 2011)
The mid-1980s discursive emergence of 'college radio' as a discrete broadcast sector in the United States was founded on college stations' embrace of UK punk during the late 1970s. While commercial rock stations rejected punk on aesthetic and affective grounds, college DJs continued to support punk's offshoots into the early 1980s, nurturing an oppositional sensibility regarding commercial broadcasting and mainstream tastes. The stunning debut of cable television channel MTV in 1981 introduced a potential crisis in self-consciously oppositional college radio communities, because as part of its programming, MTV promoted UK post-punk and 'new music' bands that had previously received most of their airplay from college stations. MTV's success sparked a parallel programming trend on commercial radio, which journalists labelled the 'New British Invasion'. The various responses to MTV and the 'New British Invasion' on the part of US college radio practitioners extended and consolidated the ethos that college radio embodied in its embrace of punk, helping to cohere the sector as a cultural imaginary. These responses also suggest that 'alternative media' theorists might profitably include college radio in the future development of alternative media models.